2021
DOI: 10.1002/ejoc.202100054
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Headed Nucleotides with Non‐Native Nucleobases: Synthesis and Duplex Studies

Abstract: Double-headed nucleotides are DNA building blocks that store, in principle, twice as much information as native nucleotides due to the incorporation of an additional functional nucleobase. Herein, we present the development of two new doubleheaded nucleotides, U W and U Z, featuring a methylene-linked 5aza-7-deazaxanthine (Z) and a propynyl-linked pseudouracil (W), respectively, attached to the 2'-position of arabinouridine. These analogs are evaluated in DNA duplexes for their ability to act as dinucleotides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…This drawback was also observed for other 2′-T monomers, 12,13 and work is currently ongoing to design a 2′-T analogue with a better specificity. 16 For the sake of completeness, the modified ON's were also hybridized to their RNA complements, however, as seen before, 10 significant destabilization of 11.0 °C to 13.5 °C were observed compared to the unmodified DNA•RNA hybrids (Fig. S16M+N, ESI †).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 69%
“…This drawback was also observed for other 2′-T monomers, 12,13 and work is currently ongoing to design a 2′-T analogue with a better specificity. 16 For the sake of completeness, the modified ON's were also hybridized to their RNA complements, however, as seen before, 10 significant destabilization of 11.0 °C to 13.5 °C were observed compared to the unmodified DNA•RNA hybrids (Fig. S16M+N, ESI †).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 69%
“…Recently, we have focused on C2' functionalized double-headed arabinonucleotides with methylene-linkers (U X , Figure 1A), as they can form WatsonÀ Crick base pairs with both nucleobases and thereby act as condensed dinucleotides in a DNA duplex. [20][21][22][23][24][25][26] Encouragingly, molecular dynamics studies have shown that local adjustments of the backbone counteract the structural alteration induced by the incorporation of a double-headed nucleotide, so that the overall B-type duplex of DNA is retained. [23] Moreover, the thermal duplex stability is not particularly affected (� 4.0 °C) [20][21][22][23][24][25] when dinucleotides are replaced with the corresponding double-headed nucleotides.…”
mentioning
confidence: 99%
“…Therefore, new monomers with non-natural nucleobases in the 2'-position were prepared and evaluated for their ability to act as improved analogues (Figure 1B). [23,26] For U T , we probed the spatial position of the thymine WatsonÀ Crick face by using hypoxanthine (U H ), [23] propynyl-linked pseudouracil (U W ) and 5-aza-7-deazaxanthine (U Z ) [26] as alternative nucleobases. However, none of these were found to be superior to the original U T monomer in terms of specificity and affinity.…”
mentioning
confidence: 99%